The European antibody network's practical guide to finding and validating suitable antibodies for research. Issue 1 (2nd January 2016) - Roncador, Giovanna; Engel, Pablo; Maestre, Lorena; Anderson, Amanda P.; Cordell, Jacqueline L.; Cragg, Mark S.; Šerbec, Vladka Č.; Jones, Margaret; Lisnic, Vanda J.; Kremer, Leonor; Li, Demin; Koch-Nolte, Friedrich; et al.
Abstract : Antibodies are widely exploited as research/diagnostic tools and therapeutics. Despite providing exciting research opportunities, the multitude of available antibodies also offers a bewildering array of choice. Importantly, not all companies comply with the highest standards, and thus many reagents fail basic validation tests. The responsibility for antibodies being fit for purpose rests, surprisingly, with their user. This paper condenses the extensive experience of the European Monoclonal Antibody Network to help researchers identify antibodies specific for their target antigen. A stepwise strategy is provided for prioritising antibodies and making informed decisions regarding further essential validation requirements. Web-based antibody validation guides provide practical approaches for testing antibody activity and specificity. We aim to enable researchers with little or no prior experience of antibody characterization to understand how to determine the suitability of their antibody for its intended purpose, enabling both time and cost effective generation of high quality antibody-based data fit for publication.